Tracing IP-spoofed packets in software defined network - Songjie WEI; Xin SUN; Rudong ZHAO; Chao WU (Tongxin xuebao, 2018)
IP packets back tracing is to find the source host hop by hop from the destination.The method found the forwarding path of target packets and source host by adding probe entry into flow tables on SDN switches and analyzing the effective back tracing Packet-in messages sent by related switches.The proposed scheme can provide convenience for debugging network problems ,so that the network administrator can obtain the forwarding paths of any data packets.Furthermore,it can help to solve the problem of IP spoofing.Experimental results prove that the traceability method can find the forwarding paths of target packets in a timely and accurate manner without affecting other traffic or significant system overhead.